Study on the Maturity Assessment Model and Application of Highway’s Standardization Management - Song Hao; Wang Xueqing; Feng Jian (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to solve the problem of highway standardization management ability description, evaluation and improvement, in this paper, a highway standardization management maturity evaluation model has firstly been put forward. Moreover, the influence highway qualitative factors of implementing the standardized management have analyzed and its evaluation index system has constructed. Furthermore, based on the practice of highway in Henan province, a standard management level has been made quantitative analysis and corresponding countermeasures and suggestions. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2856